DEPENDENCE OF THE COURSE OF ODONTOGENIC PHLEGMONS OF MAXILLOFACIAL LOCALIZATION ON CIRCADIAN RHYTHMS - Lychman, V.O.; Lokes, K.P.; Steblovskyi, D.V.; Ivanytska, O.S.; Bukhanchenko, O.P.; Stavytskyi, S.O.; Avetikov, D.S. (World of Medicine and Biology, 2023)
In the development of odontogenic phlegmons, a significant role is played by the causative microflora, general and local protective factors of organisms, anatomical-topographic features of the maxillofacial area. In addition to standard therapy, patients were prescribed intravenous administration of cryopreserved placenta extract in combination with local administration of this drug as part of Chloramphenicol-Methyluracil ointment. Patients with morning and evening chronotypes were determined according to the Khorn-Ostberg questionnaire. The among the indices of the general condition, the P-1.3 index decreased on 0.47 % on the 3rd day, the score was 67.8 %, and on the 5th day – by 0.83 % score of 83.7 % regardless of the patient’s chronotype. Among the indices of local changes in the wound, the most reliable decrease was recorded in the P-2.2 index: by 1.52 %±0.17 % on the 5th day after surgery in 83.0 % of patients with a morning chronotype who were operated on in the morning.